Revisitando Heleieth Saffioti: a construção de um conceito de patriarcado - Oliveira, Viviane Modda (2019)
The book The Woman in the class society: Myth and reality of Heleieth Saffioti (1969) is considered a milestone in women's studies in Brazil, pioneering and inaugurating an entire field of studies in the area of Brazilian sociology. The theoretical developments that involve the author's thesis of free-teaching are vast, as well as its use in feminist theory, being considered as a reference. The general objective of this research is to analyze the pioneering work of Heleieth Saffioti and its contribution, especially with the concept of patriarchy, post as an embryonic in this research. The methodology used is mainly bibliographical. The current of the book will be analyzed in this research, as well as concerns caused by it, and the non-exhaustion of the central theme that is presented. In this research, we will mobilize concepts within the area of gender studies, through a contemporary debate with a cut of theoreticians, to understand and interpret the discussions about the concept of patriarchy in sociological theory: as was used by the author and by theoretical and theoretical in the decades of 1980 and 1990 and, currently, by different perspectives of feminist theory.